A Lead Optimization of TOPK Inhibitors Using Complementary Computational and Synthetic Approaches - Manar Al-Sarhan; Lara I. Fakhouri; Nizar A. Al‑Shar'i; Tamam El-Elimat; Aref Zayed (Tabriz University of Medical Sciences, 2024)
Background: T-LAK cell-originated protein kinase (TOPK), a member of the MEK3/6-related mitogen-activated protein kinase kinase (MAPKK) family, is highly overexpressed in various cancers. This overexpression is linked to the mitotic phase of the cell cycle, highlighting its potential as a prognostic marker and therapeutic target. Unlike many other cancer targets, TOPK exhibits limited expression or is even absent in non-proliferative tissues. Therefore, TOPK inhibitors hold promise for developing anticancer agents with high selectivity and specificity for cancer cells, potentially leading to fewer side effects compared to conventional therapies. This study builds on our previous success in identifying TOPK inhibitors and aims to optimize them for improved potency. Methods: An integrated approach combining computational modeling and organic synthesis was employed. Ninety-two analogs of the lead compound (N2 ,N7 -dibenzyl-9-oxo-9H-fluorene-2,7-disulfonamide) were designed virtually and assessed for binding affinity to TOPK using docking simulations. Eight top-scoring analogs were synthesized and their inhibitory activity against TOPK was evaluated in vitro. Results: The in-silico analysis identified eight promising analogs. However, the most active synthesized analog (compound 10) exhibited moderate inhibitory activity (IC50 = 86 µM) compared to the lead compound (IC50 = 54 µM). Conclusion: While the computational approach identified potential candidates, further optimization of the synthetic analogs is necessary to achieve superior TOPK inhibitory activity. This study highlights the value of a combined computational and synthetic strategy for TOPK inhibitor development. TOPK inhibitory activity. This study highlights the value of a combined computational and synthetic strategy for TOPK inhibitor development.